PERSEPSI MASYARAKAT TERHADAP HUTAN TAMAN WISATA ALAM BIPOLO, DESA BIPOLO, KECAMATAN SULAMU, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Defryanus G. S. Kuma; Lusia Sulo Marimpan; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
Bipolo Nature Tourism park is one of the Nature Tourism Parks in Indonesia, before being designated as a Nature Tourism Park, Bipolo Forest was a production forest, with a total production area of 5.000 hectares, of the total production forest area of 5.000 hectares, an area of 352.62 hectares in the production forest area is converted into a Bipolo Nature Tourism Park since March 30, 1999 through MENHUTBUN Decree Number.161/Kpts-II/1999 concerning Establishment of Bipolo Nature Tourism Park Forest Area. The change in the status of the Bipolo Forest as a Nature Tourism Park in Bipolo Village caused a lack of attention from the management so that damage occurred such as the management of agricultural areas by the community around the forest and forest fires and illegal logging and other forest damage. From this damage resulted in the reduction of wildlife inside the Bipolo Nature Tourism. The purpose of this research is to find out the perception and the behavior of community participation in Bipolo Nature Tourism Park Forest and to find out how participation community in the management of Bipolo Nature Tourism Park, which was used in this study, the population around the Bipolo Nature Park Forest area was 83 people which determine using Purposive random sampling. The results of the in research showed that the community's attitudes and participation in the Bipolo Nature Park. In Bipolo Village, Subdistrict Sulamu, Kupang Regency, the Province of East Nusa Tenggara is in a very good category, and the level of community perceptions of the Bipolo Nature Park Forest area is in the good category while the Bipolo Nature Park Forest area is included in the neutral category.